Analisis Studi Kelayakan Bisnis pada Usaha Keripik Singkong - Berliani, Defta Nasya; Abadi, Muhammad Taufiq (BISMA : Business and Management Journal, 2023)
The industrial sector has an important role in improving the community's economic wheel. One of the food industries that can be developed and last a long time is the cassava chips business. Cassava chips are one of the snacks/snacks that are favored by all walks of life. This study aims to determine the business feasibility of cassava chips business. The author uses qualitative methods in analyzing market/marketing aspects, HR (Human Resources) aspects, socio-economic aspects and environmental aspects. This research was conducted in 20-23 March 2023 at the S3 Cassava Chips Business located in Bulakpelem Village, Sragi District, Pekalongan Regency. The results showed that the business prospects in the snack food sector, namelythe S3 Cassava Chips Business, were very good because of market demand every month. The marketing mix strategy is also very good. Production is carried out continuously for 6 days and is only closed on Sundays. There are quite a lot of human resources in this business, namely around 13 people so that it can be said to be able to develop and have long business prospects. This business also helps the community's economy and the waste produced does not harm the surrounding environment.